Ewolucja ról menedżerskich w organizacjach entrepreneurskich - Stosik, Aneta (The evolutions of management rules in entrepreneurial organizations, 2005)
The article presents results of research concerning the management of Polish small and medium sized businesses. It also contains an analysis of entrepreneurship and leadership of Polish company owners and characteristics of a business culture promoting the efficient organization of the company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 522-527